1800 - O grito da família morta: a poética pessoal na encenação de um teatro performativo - SANTOS JÚNIOR, Paulo César Sousa dos (2019)
This work is a descriptive memorial of the process of creation of the 1800 spectacle - the cry of the Morta family developed at Zecas Coletivo de Teatro, in 2017 in Belém-PA. The main purpose of this memorial is to organize the scenic creation methodology developed during this creative process. To do this, we will activate the writings of Gaston Bachelard in The Poetics of Daydream and The Poetics of Space, combining them with the personal dramaturgy of the actor of Wlad Lima and the studies of Josette Féral on the theater-performative. This writing is developed from the point of view of the director-performer of this show who uses his poetic freedom to dialogue with the person who was externalized during this creative process, presenting this cut of his memory as a Flâneur, who observes and analyzes his trajectory. In this descriptive memorandum it is exposed consecutively in its three sessions: the autobiographical poetic reveries antecedent to the scenic creation; the concepts and methodologies chosen for this creative process; and the exemplifications of the use of personal poetry in the performance of a performative theater.